Dynamic Perturbations of CD4 and CD8 T Cell Receptor Repertoires in Chronic Hepatitis B Patients upon Oral Antiviral Therapy - Xu, Ying; Liu, Yu; Zhao, Miaoxian; Chen, Yunqing; Xie, Cantao; Gong, Mingxing; Deng, Haohui; Li, Xueying; Sun, Jian; Hou, Jinlin; Wu, Hongkai; Wang, Zhanhui (Frontiers in Immunology, 2017)
Long-term treatment with nucleos(t)ide analogues (NUCs) can improve the antiviral T cell response in chronic hepatitis B (CHB) patients. Whether and to what extent the T cell response is improved by NUCs in the early stage leading to hepatitis B e antigen (HBeAg) seroconversion remain to be clarified. A total of 22 CHB patients undergoing 2-year telbivudine-based therapy were enrolled, including 10 exhibiting a complete response (CR) and 12 exhibiting a non-complete response (NCR) according to HBeAg seroconversion at week 52. Peripheral CD4+ and CD8+ T cells were sorted at baseline, weeks 12 and 24. The T cell receptor β chain (TCRβ) complementarity-determining region 3 (CDR3) was analyzed by unbiased high-throughput sequencing. Compared with NCR group, patients in CR group had a much lower percentage of persistent clonotypes (P<0.001) but remarkably higher percentages of new and expanded clonotypes (P<0.05) between any two time points for both CD4 and CD8 subsets. The CD4 T cells exhibited a stronger response than CD8 population in the patients. The number of new and expanded clonotypes was inversely associated with the decline of viral antigen. In conclusion, NUC-based therapy induces a broad and vigorous T cell response with rapid decline of antigenemia during the early stage of treatment. A broad T cell expansion is crucial for HBeAg seroconversion. Our findings suggest that the potent suppression of hepatitis B virus replication by NUC monotherapy complemented with additional immunomodulatory strategies may increase the likelihood of a functional cure for CHB in the future.